Cultivating Interest In Postpartum Exercise Through Screens: A Study Of Video Education For Pregnant Women At Blabak Community Health Center - Yunita Anggraini; Koekoeh Hardjito; Lumastari Ajeng Wijayanti; Indah Rahmaningtyas (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
Postpartum hemorrhage remains a major contributor to maternal mortality. Engaging in postpartum exercise is one preventive measure, as it stimulates uterine contractions and helps reduce bleeding. However, many postpartum mothers are reluctant to perform these exercises due to pain perception and fear of movement. Providing health education during pregnancy is a potential strategy to increase their interest. This study aimed to analyze the effect of video-based health education on pregnant women’s interest in postpartum exercise. The research applied a quantitative pre-experimental approach using a one-group pretest–posttest design. The population consisted of third-trimester pregnant women (>37 weeks gestation) in the working area of the Blabak Community Health Center. A total of 34 respondents were selected through proportionate stratified random sampling. Data were collected using a validated 22-item questionnaire administered before and after the intervention. The intervention involved structured health education delivered through video media, and data were analyzed using the Wilcoxon Signed-Rank Test with a significance level of 0.05. The findings indicated a statistically significant increase in interest in postpartum exercise after the intervention (p = 0.001). It can be concluded that video-based health education is effective in enhancing pregnant women’s interest in performing postpartum exercise after childbirth.